Cost-effectiveness of personalised telehealth intervention for chronic disease management: A pilot randomised controlled trial. - Shalika Bohingamu Mudiyanselage; Jo Stevens; Julian Toscano; Mark A Kotowicz; Christopher L Steinfort; Robyn Hayles; Jennifer J Watts (PLoS ONE, 2023)
Objective The study aims to assess the cost-effectiveness of a personalised telehealth intervention to manage chronic disease in the long run. Method The Personalised Health Care (PHC) pilot study was a randomised trial with an economic evaluation alongside over 12 months. From a health service perspective, the primary analysis compared the costs and effectiveness of PHC telehealth monitoring with usual care. An incremental cost-effectiveness ratio was calculated based on costs and health-related quality of life. The PHC intervention was implemented in the Barwon Health region, Geelong, Australia, for patients with a diagnosis of COPD and/or diabetes who had a high likelihood of hospital readmission over 12 months. Results When compared to usual care at 12 months, the PHC intervention cost AUD$714 extra per patient (95%CI -4879; 6308) with a significant improvement of 0.09 in health-related quality of life (95%CI: 0.05; 0.14). The probability of PHC being cost-effective by 12 months was close to 65%, at willingness to pay a threshold of AUD$50,000 per quality-adjusted life year. Conclusion Benefits of PHC to patients and the health system at 12 months translated to a gain in quality-adjusted life years with a non-significant cost difference between the intervention and control groups. Given the relatively high set-up costs of the PHC intervention, the program may need to be offered to a larger population to achieve cost-effectiveness. Long-term follow-up is required to assess the real health and economic benefits over time.